Community service in order to strengthen the values of Pancasila - Hastangka, Hastangka; Ratmanto, K.R.A.P. Eri (Community Empowerment)
Pancasila is the basis of the state and the way of life of the Indonesian people. Pancasila as the basis of life as a nation and state is important to be continuously socialized and introduced to the community because the dynamics and changes of society from time to time affect the perspective and attitude of behavior in the life of the nation and state. After the reformation, Pancasila as the value of life for the nation and state was neglected because of the political situation and conditions of reform that focused on democracy, civil supremacy, and upholding human rights. This reduces the role and function of Pancasila in the life of the nation and society. Starting in 2009, a socialization program for the 4 Pillars of Nationality emerged by the People's Consultative Assembly of the Republic of Indonesia. The program wanted to introduce Pancasila, but the use of the term became a problem because it included Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia, and Bhinneka Tunggal Ika as pillars. The program created by the MPR RI has evolved into the 4 Pillars of the MPR RI. This community service activity aims to educate and strengthen Pancasila values through correct literacy of the history of Pancasila to the community. Pancasila is the basis of the Unitary State of the Republic of Indonesia, not a pillar. The model of community service activities is carried out by media education and discussions to the community. The forms of activities carried out are parades and discussions with community and community leaders about the importance of Pancasila as the basis of the state and not pillars which will be held in January-March 2021. The results of this service activity show that first, the public in general does not know developments about Pancasila and its dynamics. which exists. Second, after the socialization of Pancasila values as the basis of the state, people began to understand and understand the development and dynamics of Pancasila. Third, the efforts to raise awareness about the correct knowledge of Pancasila are important for the community.